MiDAS COMMITTED TO COLLABORATE WITH USM IN WHEELCHAIR PROJECT - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 Malaysian Institute of Defence and Security (MiDAS) has expressed its desire to collaborate with Universiti Sains Malaysia (USM) in developing the wheelchair project to provide specially modified wheelchairs to underprivileged people with disabilities (PwD).